Rheological, Mechanical and Adhesive Properties of Surfactant-Containing Systems Designed as a Potential Platform for Topical Drug Delivery - Carvalho, Flavia Chiva [UNESP]; Rocha e Silva, Hilris [UNESP]; da Luz, Gabriela Marielli [UNESP]; Barbi, Mariana da Silva [UNESP]; Landgraf, Daniele Silveira [UNESP]; Chiavacci, Leila Aparecida [UNESP]; Vitorino Sarmento, Victor Hugo; Gremião, Maria Palmira Daflon [UNESP] (Amer Scientific Publishers, 2012)
In the last few decades, nanotechnology has led to an advance in the development of topical drug delivery. Nanostructured drug delivery systems enable the compartmentalization of drugs in restricted environments, modifying the release profile and maintaining the required drug concentration for prolonged periods at the site of action and/or absorption. The development of nanostructured systems containing surfactants has evolved rapidly. Mixtures of surfactant, oil and water can self-associate to form structures, such as microemulsions and liquid crystal phases, which can be exploited as drug delivery systems because their nanostructured organization can control drug release. Therefore, the purpose of this study was to assess the potential of systems containing polyoxypropylene (5) polyoxyethylene (20) cetyl ether as surfactant, oleic acid or mineral oil as the oily phase, and water to be used as a platform in the development of topical drug delivery systems. Physicochemical characterization of the systems was performed by polarized light microscopy (PLM), small-angle X-ray scattering (SAXS), rheological tests and texture profile analysis. The ternary phase diagrams showed that combinations of surfactant/mineral oil/water and surfactant/oleic acid/water could form various thermodynamically stable structures, such as microemulsions and liquid crystals. The oily phases, oleic acid and mineral oil, changed the rheological, mechanical and adhesive properties of systems containing polyoxypropylene (5) polyoxyethylene (20) cetyl ether.
Keywords: Nanotechnology; Topical Drug Delivery; Surfactant; Microemulsion; Liquid Crystal; Mineral Oil; Oleic Acid